2015
DOI: 10.3329/pa.v26i2.25964
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of root crops with chilli in charlands of Mymensingh

Abstract: Adoption of intercropping may increases crop production instead of declining trend of agricultural land in Bangladesh. Thus, a field experiment on intercropping of root crops with chilli was executed at char area of Dori Bhabkhali in Mymensingh district during October 2014 to March 2015 to find out an appropriate intercrop for cultivation with chilli for higher productivity and maximum economic return. The experiment was consisted with five crop combinations viz., sole chilli, chilli + radish, chilli+ carrot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…(283.45 g), minimum fruit yield hectare -1 (9.45 t) was recorded in T 6 (Chilli @ 100% + Radish + Beetroot). Similarly, Begum et al, [3]; Ahmed et al (2013) reported negative impact of intercropping on main crop. Likewise, the maximum TSS value (8.10 ºBrix) was observed in T 1 (Sole chilli @ 100% RDN) while the minimum TSS value (7.37 ºBrix) was observed in T 6 (Sole chilli @ 100% RDN + Radish + Beetroot).…”
Section: Growth Yield and Quality Characters Of Chillimentioning
confidence: 86%
“…(283.45 g), minimum fruit yield hectare -1 (9.45 t) was recorded in T 6 (Chilli @ 100% + Radish + Beetroot). Similarly, Begum et al, [3]; Ahmed et al (2013) reported negative impact of intercropping on main crop. Likewise, the maximum TSS value (8.10 ºBrix) was observed in T 1 (Sole chilli @ 100% RDN) while the minimum TSS value (7.37 ºBrix) was observed in T 6 (Sole chilli @ 100% RDN + Radish + Beetroot).…”
Section: Growth Yield and Quality Characters Of Chillimentioning
confidence: 86%
“…Additional yield of companion crops having a good market price mainly contributed to increase the profitability of intercropping systems over sole pumpkin. Begum et al (2015), Hossain et al (2015), Akhtar et al (2015), Islam et al (2014) and Ahmed et al (2013) also reported that intercropping gave higher productivity and economic returns compared to monoculture. 10.7 Price of input (US $ kg -1 ): Urea: 0.24, TSP: 0.27, MOP: 0.21, Gypsum: 0.12, Zinc sulphate: 2.20 and Boric acid: 4.27, pumpkin seed: 3.66, radish seed: 2.44, red amaranth seed: 2.44, coriander seed: 159, mustard seed: 1.04, spinach seed: 2.44, labour: 3.66 US $, land lease: US $ 40.24 bigha -1 1 US $ = 82 BDT…”
Section: Economic Performancesmentioning
confidence: 94%
“…Usually plants differing in growth duration, height, rooting systems and nutrient requirements are considered to grow together in intercropping systems (Reddy and Willey, 1981). The system becomes more productive and profitable by selecting appropriate crops, population density and planting geometry of component crops (Alom et al 2014;Begum et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The higher yield advantage of the intercrops over the sole stand might be resulted from the compatibility of the component crops for efficiently utilization of the growth resources viz., light, moisture and nutrients [43,51,[53][54][55]. In addition, the result could be associated with the different root and shoot structures of coffee and enset plants, which results different competitive ability of the component crops for growth resource utilization [21,56]. The findings of this study in agreement with the previous research works of Kufa et al [3], Taye et al [4], Anteneh et al [5] and Taye et al [40].…”
Section: The Yield Advantage Of Coffeementioning
confidence: 99%
“…Therefore, the alert of the small farm size owned by farmers, the prolonged time and shade requirements of coffee trees for crop bearing, intercropping is the only remedy to increase the productivity of the component crops and land-use efficiency. It has been also reported that the diversification of coffee with compatible crop types would be the right option for better resource use efficiency and productivity [4,5,20,21]. Despite its economic and social advantage, the effects of coffee-enset intercropping on the yield productivity of the component crops have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%